Gregor and the Prophecy of Bane - Collins, Suzanne (New York : Scholastic Inc., 2004)
In his second adventure, eleven-year-old Gregor returns to the world beneath New York City to rescue his kidnapped sister, Boots, and fulfill a prophecy that will restore peace to the people, bats, rats, cockroaches, and spiders who populate the underworld.
Sequel to: Gregor the overlander.
Sequel: Gregor and the curse of the warmbloods.
G4
Keywords: Friendship -- Fiction; Brothers and sisters -- Fiction; Animals -- Fiction; Fantasy